Implikasi Yuridis Ekonomis Penetapan Hak Kekayaan Intelektual sebagai Bundel Pailit dalam Sistem Hukum Indonesia - Bakhtiar Jangkap Jaya (Jurnal Hukum Lex Generalis, 2025)
This study examines the juridical and economic implications of classifying Intellectual Property Rights (IPR) as part of the bankruptcy estate under Indonesian law. As intangible assets with strategic economic value in a knowledge-based economy, IPR can serve as a source of debt repayment when a debtor is declared bankrupt. However, tensions arise between ensuring legal certainty for creditors and protecting the inalienable moral rights of creators. Using a normative juridical approach, this research analyzes the interrelation between bankruptcy law and property law to clarify the position of IPR within the bankruptcy estate. The findings indicate that although IPR can enhance creditors’ guarantees, the absence of clear technical rules regarding appraisal, management, and auction procedures creates legal uncertainty. Therefore, regulatory reform is necessary to balance creditors’ interests, the protection of moral rights, and business continuity within the framework of modern bankruptcy practices.